A new strategy for lung cancer treatment: Biotin-coated drug delivery system loaded with 5-fluorouracil and gentisic acid - Poyraz, Fatma Sayan; Mansuroglu, Banu (ELSEVIER SCI LTD, 2025)
Lung cancer continues to pose a significant therapeutic challenge due to its high mortality rate and the systemic toxicity associated with conventional chemotherapeutics. Addressing the urgent need for more selective and effective treatment strategies, this study presents the design and development of a novel bio-based nanotherapeutic product: biotin-functionalized poly(lactic-co-glycolic acid) nanoparticles (BNPs) co-loaded with 5Fluorouracil (5-FU) and Gentisic Acid (GA). This dual-drug-loaded nanosystem was engineered to enhance intracellular delivery and therapeutic precision against A549 non-small cell lung cancer cells, which express biotin-positive receptors on their surface. Physicochemical characterization using FT-IR, XRD, SEM, and TEM confirmed the successful fabrication of uniform and stable nanoparticles with appropriate size and surface properties. In vitro experiments demonstrated that BNPs exhibited significantly enhanced anticancer activity compared to non-targeted nanoparticles and free drug combinations, with a notably low IC50 value of 0.35 mM after 48 h of treatment. BNPs also effectively inhibited cell viability, migration, proliferation, and colony formation, while inducing apoptosis, autophagy, oxidative stress, and mitochondrial dysfunction-hallmarks of targeted cancer cell death. By integrating biotin-mediated targeting with a synergistic dual-drug strategy, this study introduces a promising and innovative bio-product candidate for the selective treatment of lung cancer, offering a new direction for advanced, precision-oriented nanomedicine platforms.
Keywords: 5-fluorouracil; Gentisic acid; Biotin; Nanoparticle; Targeted nanoparticle; Lung cancer; PLGA NANOPARTICLES; POLYMERIC NANOPARTICLES; TARGETED DELIVERY; CO-DELIVERY; RELEASE; PROLIFERATION; CYTOTOXICITY; EFFICACY; THERAPY; Biochemistry & Molecular Biology; Biotechnology & Applied Microbiology; Engineering